The Importance of Developer Reputation Criterion In House Purchase Decision Making - Ahmad Taufik Nursal; Mohd Faizal Omar; Mohd Nasrun Nawi; Mazlan Mohd Sappri (International Journal of Supply Chain Management, 2019)
House purchase is high stake decision that is not only required a high number of investment, yet numerous criteria need to be considered. Such as price, location, neighborhood, infrastructure, future value, availability of green space, developer reputation, transportation and etc. However, due to the increasing number of failed and unfinished housing project mostly caused by developer, the role of developer reputation criterion is becoming increasingly important in housing selection. Thus, this paper had provided insight on how reputation criteria influence housing purchasing decision making. In addition, this paper has gathered evidences to illustrate the needs of developer reputation decision making tools towards a better decision-making process. It is anticipates that this study will yield an effective decision making platform to manage housing purchase problem.